HE STOOD AT SOURCES OF A NEW MATHEMATICAL DISCIPLINE – TOPOLOGIES: To 55 - anniversary of departure in Eternity of the prominent Ukrainian mathematician and teacher, actual member of Scientific society named by Shevchenko Myron Zarytsky - Зарічний, Михайло Михайлович; Пташник, Богдан Йосипович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A vital and scientific way and basic results is described in industry of topology of Myron Zarytsky – the prominent Ukrainian mathematician, actual member of Scientific society the named by Shevchenko, professor of Lviv university.